Factors Associated with Stunting in Toddlers Aged 0-59 Months in Bonomerto - Aditya Marzuq Dermawan; Noor Alis Setiyadi (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Stunting is a health problem that hinders human growth and development globally. It is important to raise awareness about the importance of nutrition during pregnancy and child growth, as well as provide support and education to pregnant women and society in general. Preventive efforts and early intervention can help overcome the problem of stunting and improve children's overall health. This study was designed to determine the factors associated with the incidence of stunting in toddlers aged 0-59 months in Bonomerto, Suruh District, Semarang Regency. This research is quantitative with a cross sectional research design. This research was conducted in June-July 2023. The research was carried out in Bonomerto Village, Suruh District, Semarang Regency. The population in this study was 224 mothers who had toddlers aged 0-59 months in Bonomerto Village, Suruh District, Semarang Regency. The sampling technique used was using the Random Sampling technique, so that the sample in this study was 144 toddlers. The instrument used in this research was a questionnaire. Data analysis in this study was analyzed using the chi-square test. The research results showed that there was a relationship between maternal education (p=0.000), family income (p=0.000), Antenatal Care Visits (p=0.000), baby birth weight (p=0.004) with the incidence of stunting in toddlers aged 0-59 months. It is recommended for mothers to carry out regular antenatal care visits and early detection of the risk of stunting in the fetus at health facilities and for health workers to provide education about the importance of prenatal checks for pregnant women in order to reduce the incidence of stunting risk. Keywords: Antenatal care visits, Breastfeeding, Stunting, Toddlers